Pengaruh Kelompok Acuan Terhadap Minat Beli Konsumen (Studi pada Konsumen Yamaha NMAX di Kota Bandung) - Agri Regiansa; Dadan Abdul Aziz Mubarok (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2020)
This study aims to determine how respondents respond to the Reference Group and Buying Interest, and to see how much influence the Reference Group has on Buying Interest. The method used in this research is quantitative method. Data collection was carried out through a literature study and distributing questionnaires to 102 respondents. Sampling with purposive sampling. Data analysis uses simple Smart PLS analysis. The results showed that: Respondents' responses to the Reference Group, and Purchase Interest were in the good category by showing the results that the Reference Group had a strong positive effect on Buy Interest. The results of R Square, show that the magnitude of the influence of the Reference Group on Buying Interest is 32.1%, the remaining 67.9% is influenced by variables not examined in this research model.